2021
DOI: 10.3390/ijms22189742
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Study of the Impact of Focal Blue Light-Emitting Diode-Induced Phototoxicity in Adult Albino Rats

Abstract: Background: In adult rats we study the short- and long-term effects of focal blue light-emitting diode (LED)-induced phototoxicity (LIP) on retinal thickness and Iba-1+ activation. Methods: The left eyes of previously dark-adapted Sprague Dawley (SD) rats were photoexposed to a blue LED (20 s, 200 lux). In vivo longitudinal monitoring of retinal thickness, fundus images, and optical retinal sections was performed from 1 to 30 days (d) after LIP with SD-OCT. Ex vivo, we analysed the population of S-cone and Iba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(85 reference statements)
0
5
1
Order By: Relevance
“…Albino rats exposed to low-intensity light for 10 days showed transient changes in b-wave amplitudes, a-wave sensitivity, and CFF values. These changes were markedly different from the results obtained previously, detailing the permanent loss of the rodand cone-driven ERG flicker signal in aging RCS rats [18] and more severe forms of light damage in albino animals [17,19,20]. We found a uniform reduction in the ONL from the superior to the inferior retina, whereas others have noted focal damage under their conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Albino rats exposed to low-intensity light for 10 days showed transient changes in b-wave amplitudes, a-wave sensitivity, and CFF values. These changes were markedly different from the results obtained previously, detailing the permanent loss of the rodand cone-driven ERG flicker signal in aging RCS rats [18] and more severe forms of light damage in albino animals [17,19,20]. We found a uniform reduction in the ONL from the superior to the inferior retina, whereas others have noted focal damage under their conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…The goal of this experiment was to characterize the etiology of decreased cone-driven vision in the light damage model of retinal degenerations. Because most retinal degenerations are typically categorized as “rod” diseases, fewer efforts have been directed toward the effects of light damage on the cone photoreceptors in chronic light exposure models, although recent studies have looked at focal, blue light and LED damage to cones [ 15 , 26 ]. By analyzing and comparing visual functional changes (via ERG), in vivo histology (via OCT), and in vitro histology (via immunohistochemistry), our study provides an investigation of cone density changes as well as rod loss resulting from low-level, long-duration light damage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown [14] that IL-6 and TNF-α are expressed in the ocular surface tissues of rats with exorbital lacrimal gland-excision, indicating the IL-6 and TNF-α play an important role in the pathogenesis of the dry eye. It's widely known that the most harmful component of visible light is the blue wavelength (400-500 nm) that can potentially harm eye tissues [15][16] , especially the retina [17] , which can cause inflammation, angiogenesis and so on [18] . Vicente-Tejedor et al [19] removed the blue component of light and found it significantly decreased retinal damage after high intensity exposure.…”
Section: Discussionmentioning
confidence: 99%